Development of ECU (Electronic Control Unit) to Maintain Stability of Biogas Fuelled Generator - Totok Soehartanto; Dwi Nur Fitriyanah; Putri Yeni Aisyah (IPTEK The Journal of Engineering, 2020)
Biogas fueled generator has a unique character because the converter kit on the generator has the characteristic of absorbing the biogas supply. Therefore, in this study, biogas is accommodated in a plastic container equipped with a valve that can adjust the amount of biogas supply pressure. Combustion in the Genset combustion chamber will occur if the ratio of air supply and supply of biogas (AFR = Air to Fuel Ratio) meets the stoichiometric number. So a ratio control is needed on air supply and biogas supply, which can follow changes in biogas conditions in plastic bags and generator loads. For this reason, this paper presents an ECU (Electronic Control Unit) that can regulate the ratio of air supply to biogas supply by using a servo motor valve, which is commanded by a control signal from the ECU. The resulting ECU prototype is equipped with a multi-input connector (to receive the signal output of CH4 methane gas sensor and the biogas supply pressure sensor), multi-output (control signal to the servo motor valve), and multi regulators to adjust the Set Point value for the methane gas content CH4, the value of the set point of the biogas supply pressure and to tune the value of the proportional gain control (KP). The results of the ECU performance test by trial and error by giving a dummy input signal (analogy to the signal output of methane gas sensor and the analog of the pressure sensor output signal in the form of an electric voltage generated from the signal generator) can drive the servo motor, valve air supply, and servo motor, valve supply biogas. Accordance with the gain control input from the regulator.